In search of gender bias in household resource allocation in rural China - Lina Song (Institute for the Study of Labor (IZA), 2008)
This paper tests three hypotheses concerning intra-household resource allocation in rural China. First, whether increasing the women's bargaining power alters household expenditure patterns. Second, whether households allocate fewer resources to daughters than to sons. Third, whether increasing the bargaining power of women reduces pro-boy discrimination. We find that expenditure patterns do vary with proxies for women's bargaining power. Pro-boy discrimination is suggested by: lower female outlay equivalent ratios for adult goods; greater sensitivity of household health spending to young boys than to young girls; and high male sex ratios. No evidence is found to support the third hypothesis.
urn:nbn:de:101:1-20080421216
Keywords: D1; 330; Intrahousehold allocation; women; bargaining power; China; Verbraucherausgaben; Diskriminierung; Geschlecht; Landbevölkerung; Mädchen; China